Success and Safety of Plastic Stent for Endoscopic Ultrasound Guided Pancreatic Pseudocyst Drainage - A Tertiary Single Centre Experience - Khattak, Muhammad Bilal; Khan, Zoya Ali; Khan, Uzair Ali; Ali Khan, Rao Saad; Shabbir, Khawar; Chauhadry, Qurat-ul-Ainy (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the success and safety of plastic stent for endoscopic ultrasound (EUS) guided pancreatic pseudocyst (PP) drainage. Study design: Quasi-experimental study Place and duration: Pak-Emirates Military Hospital Rawalpindi, Pakistan from Jan 2018 to Jan 2021 Methodology: This study was conducted on seventy three participants with 20-80 years age, both genders, and symptomatic PP. Cases having small asymptomatic PP (<5cm), neoplastic cysts, multiloculated pseudocysts, coagulation profile derangement were excluded. EUS -guided drainage of PP was done. Success and safety of the procedure and post procedure compression related problems (PPCRP) were recorded at 24 hours, and at 4, 8, 12 and 24 weeks. Chi-square test was used to determine the association of PPCRP with biochemical and cytological parameters. Results: The mean age was 45.38±12.79 years and 44 (60.27%) were males. In all participants, there was a 50.00% regression in cyst size at 4, 8, 12, and 24 weeks. Significant factors affecting PPCRP at 8 weeks were complicated pancreatic pseudocysts (PP), cystic haemorrhage, portal hypertension (on CT), and cystic location (on EUS). At 8 weeks, no resolution of compression-related problems was found in cases of complicated cysts (0%), and the results were statistically significant (p<0.001). The highest resolution in compression-related problems at 8 weeks was found when the cyst was located in the head (n=19, 61.29%) followed by the .. Conclusion: Endoscopic ultrasound guided drainage of PP is an effective treatment modality having 50% regression in size after one month in all patients.